Socio-philosophical analysis of the harmony of youth social activity and innovative potential in modern conditions (Zien Journal of Social Sciences and Humanities, 2026)
This article discusses scientific issues related to the process of harmoniously improving the social activity and innovative potential of young people. The article highlights the social significance of the manifestation of progressive initiatives, intellectual development, social, cultural and educational advancement of young people. It also examines the factors related to the manifestation of creative and innovative qualities of young people in society